Frequency of impaired glucose tolerance and its correlates in females of reproductive age in urban slums of Lahore, 2019 - Filza Haqiq; Seema Imdaad; Tajammal Mustafa; Ata-ur-Rahman; Umar Farooq; Maryam Fatima; Tasneem F Rana; Javaria Anwer (Journal of Family and Community Medicine, 2023)
BACKGROUND: The prevalence of diabetes mellitus has almost reached global epidemic proportions. Fortunately, the progress of the disease can be stemmed at the prediabetic level. The objective of the present study was to determine the frequency of impaired glucose tolerance (IGT) and its predictors in females of reproductive age in the urban slums of Lahore. MATERIALS AND METHODS: A cross-sectional study was conducted among females of reproductive age in the slums of metropolitan Lahore. The calculated sample size was 384. Data were collected using a structured questionnaire covering demographic variables, lifestyle, medical, and dietary history. The oral GT test was carried out on the study participants after a 10 hour overnight fasting. Data were entered and analyzed using Statistical Package for the Social Sciences (SPSS version 23). Frequency distributions and percentages were calculated for categorical variables, and the mean and standard deviation were calculated for continuous variables. The Chi-square test or Fisher's exact test, as appropriate, was used to determine the association between IGT and various categorical variables. Logistic regression analysis was performed to determine the correlates of IGT after adjusting for confounders. RESULTS: The final sample size was 394 women; 17% of whom had IGT, and 8.6% had newly diagnosed diabetics. Results of logistic regression showed increased waist/hip ratio, lower literacy of father or husband, age, and low intake of pulses as significant predictors of IGT (P < 0.05). CONCLUSION: The frequency of IGT is high in females of reproductive age living in the urban slums of Lahore. There is a need for targeted health promotion and educational activities to improve the health and social conditions of slum dwellers.